A Summary of Preclinical Poster Presentations at the Sixth Biennial Pediatric Anesthesia Neurodevelopment Assessment (PANDA) Symposium. Issue 1 (January 2019) - Griffiths, Keren K.; Morgan, Philip G.; Johnson, Simon C.; Nambyiah, Pratheeban; Soriano, Sulpicio G.; Johnson, Kenneth; Xu, Jing; Garber, Carol; Maxwell, Lynne; Saraiya, Neeta
Abstract : The potential for long-term neurotoxic effects of anesthetics on the developing human brain has led to intensified research in this area. To date, the human evidence has been inconclusive, but a large body of animal evidence continues to demonstrate cause for concern. On April 14 and 15, 2018 the sixth biennial Pediatric Anesthesia and Neurodevelopmental Assessment (PANDA) study symposium was held at Morgan Stanley Children's Hospital of New York. This symposium brought together clinicians and researchers and served as a platform to review preclinical and clinical data related to anesthesia and neurotoxicity in developing brains. The program participants included many active investigators in the field of anesthesia neurotoxicity as well as stakeholders from different backgrounds with the common interest of potential anesthetic neurotoxicity in children. The moderated poster session included presentations of preclinical animal research studies. These studies focused on defining the anesthetic-induced neurotoxicity phenotype, understanding the mechanism of injury and discovering potential inhibitors of neurotoxic effects.